Determinants and measurement of quality of life in patients with inflammatory bowel disease: a systematic review - Makhdzir, Norafisyah; Chen, Hongyun; Wang, Lining; Haron, Zarina (Rawal Medical Journal, 2024)
Objective: To explore the determinants of quality of life in patients with inflammatory bowel disease and evaluate the specific measurement instruments used. Methodology: A systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were performed across five databases: PubMed, Scopus, Web of Science, Embase, and Google Scholar. Studies published between January 1, 2004, and January 1, 2024, that utilized validated QoL measurement tools and statistically analyzed associated factors were included. Results: The 19 included studies summarized three main dimensions that affect quality of life: social dimension, physical dimension and psychological dimension. Conclusion: Despite significant progress in understanding the quality of life of patients with inflammatory bowel disease , notable limitations persist. QoL is influenced by the complex interplay of social, physiological, and psychological factors. While existing measurement tools are reliable, they vary in sensitivity, particularly in capturing individual patient experiences and specific symptoms such as fatigue. Moreover, uneven geographical distribution of studies, a lack of large-scale longitudinal research, and underrepresentation of key populations hinder a comprehensive understanding of the chronic progression and diverse needs of IBD patients. In clinical practice, a multifaceted assessment approach is essential for accurately evaluating QoL. Future efforts should prioritize patient-centered strategies, including the development of more specific tools to address these gaps and implement targeted interventions to effectively enhance the QoL of IBD patients.